Imagining a Hellenic Republic, 1797–1824: Rigas, Korais, Byron. (June 2018) - Beaton, Roderick
Abstract : The 'New Constitution' for a Hellenic Republic, published in Vienna by Rigas Velestinlis in 1797, was modelled closely on the French republican constitution of 1793, and envisaged what is now called a 'civic nation' based on inclusiveness and the 'Rights of Man'. Rigas was arrested by the Austrian authorities, handed over to the Ottomans, and executed the following year. The turn from 'civic' to 'ethnic' nationalism among Greeks in the years leading up to the successful Revolution of 1821 is marked in the work of the influential classical scholar and national ideologue Adamantios Korais (Koraes, or Coray). Lord Byron, visiting Greek lands between 1809 and 1811, saw evidence for the enthusiasm with which Rigas was remembered and Korais was revered by the Greeks he met, and one of his early published works is a piece of revolutionary doggerel that at the time was attributed to Rigas. Byron's later determination to exchange the 'words' of the poet for the 'things' achieved by a statesman and man of action can be traced back to these early experiences in Greece – as well as to his ambivalent admiration for the more moderate among the leaders of the Revolution in France.